LANSIA DALAM SENI LUKIS KUBIS - Fadhil Irsyad; Efrizal Efrizal (Serupa The Journal of Art Education, 2021)
Purpose of making the final work is to visualize the anxiety about the life of the elderly through a cabbage-style painting so as to deepen the concept and mature painting techniques. The method used in the final work uses five stages, namely the preparation stage, the elaboration stage, the synthesis stage, the concept realization stage, and the completion stage. The ten works visualized represent the title of the final work. So that ten works were created that visualize anxiety about the life of the elderly with the following titles: 1)“Sebatang Kara”. 2) “ Malu Aku Mak”. 3) “ Alat Tua”. 4) “ Pasangan Tua”. 5) “Penantian di Panti Jompo”. 6), “Lansia Tersesat”. 7) “Tak Terurus”. 8) “Pedagang Lansia”. 9) “Lansia Tunawisma”, 10) ”Lansia Tunanetra”.Kata Kunci : Lansia dalam Seni lukis, Gaya Kubis.